2011
DOI: 10.4330/wjc.v3.i6.169
|View full text |Cite
|
Sign up to set email alerts
|

Nifekalant in the treatment of life-threatening ventricular tachyarrhythmias

Abstract: The aim of the present study is to review the literature and discuss nifekalant's potential use as a first aid drug in an emergency care setting. The PubMed database was used to identify papers, using keywords nifekalant, MS-551, amiodarone and lidocaine. Nifekalant hydrochloride, formally known as MS-551, is a class Ⅲ antiarrhythmic agent which acts only by increasing the time course of myocardial repolarization. It was developed and is currently being used only in Japan for the treatment of ventricular tachy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Sotalol has a similar effect but causes beta‐adrenergic blockade, which is contraindicated in bradycardic patients. Although several studies on nifekalant have been reported thus far, in most of them, including our study, a comparison among antiarrhythmic drugs was difficult because of an insufficient numbers of patients and heterogeneous study designs [22].…”
Section: Discussionmentioning
confidence: 92%
“…Sotalol has a similar effect but causes beta‐adrenergic blockade, which is contraindicated in bradycardic patients. Although several studies on nifekalant have been reported thus far, in most of them, including our study, a comparison among antiarrhythmic drugs was difficult because of an insufficient numbers of patients and heterogeneous study designs [22].…”
Section: Discussionmentioning
confidence: 92%
“…Amiodarone and nifekalant are both classified as class III antiarrhythmic agents (potassium channel blockers) in the Vaughan‐Williams classification [ 14 , 15 ]. However, these two class III antiarrhythmic drugs have different pharmacological characteristics.…”
Section: Characteristics and Evidence Of The Efficacy Of Antiarrhythmmentioning
confidence: 99%
“…We previously studied molecular mechanisms of drug interactions with structural models of the hERG channel in inactivated states ( Maly et al, 2022 ). In this study, we used Rosetta computational modeling software to study atomic-level interactions between the hERG channel in an open and closed state and drugs with relatively low (amiodarone and nifekalant), intermediate (flecainide and moxifloxacin), or high (d/l-sotalol and dofetilide) risk for arrhythmia ( Doggrell, 2001 ; Kang et al, 2001 ; Pantazopoulos et al, 2011 ; Haverkamp et al, 2012 ; Barman, 2015 ; Furutani et al, 2019 ; Orvos et al, 2019 ; Mujovic et al, 2020 ; DeMarco et al, 2021 ). The structural models of an open-state wild-type (WT) hERG channel, its mutants (Y652A, F656A, and Y652A/F656A double mutant), and the closed-state WT hERG channel ( Figure 1 ) were developed as targets for docking studies of cationic and neutral forms of the drugs ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data suggest that F656 and Y652 in the S6 segment and S624 at the base of the selectivity filter (SF) play key roles in the ability of amiodarone to block hERG channels ( Zhang et al, 2016 ). Nifekalant is a pyrimidinedione-based class III antiarrhythmic drug used in the treatment of ventricular tachycardia ( Pantazopoulos et al, 2011 ). It is a high-affinity hERG blocker with reported IC 50 values of ∼70–145 nM ( Kushida et al, 2002 ; Ridley et al, 2004 ; Furutani et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%